Profil Karakter Peduli Lingkungan Peserta Didik Kelas X SMA Negeri 1 Karangrayung Kabupaten Grobogan - Paryumi Paryumi (Jurnal Kualita Pendidikan, 2021)
It is important to know the environmental care character of students to evaluate the extent to which the Adiwiyata program has a positive influence on students' attitudes to be more concerned about the environment. Therefore, this study aims to analyze how the profile of environmental care characters in SMA Negeri 1 Karangrayung students, Grobogan Regency. This research is a qualitative descriptive study. The subjects in this study were students. The sample used consisted of two class X SMA Negeri 1 Karangrayung, Grobogan Regency which were determined randomly. Questionnaires were used to dig up information about the character of environmental care in students. The results showed that students at SMA N 1 Karangrayung had the best attitude towards environmental care on the attitude indicator towards waste, followed by the attitude indicator towards the social and human environment, the attitude indicator towards energy, the attitude indicator towards air, land and water, and the lowest. is an attitude towards flora and fauna. Based on the results of the analysis, it can be concluded that the highest environmental care character of students is in the good category which is 96.92%, and the low category is 3.07%, meanwhile there are no students with very good attitude categories and apathy or apathy. does not matter.